Epistemologi Bayani, Irfani, Burhani dalam Al-Jabiri Terhadap Kritik Nalar Arab dan Korelasinya dengan Pendidikan Islam - Huda, Luthfi Nurul; Linda, Linda; Syihabuddin, Muhammad; Firmansyah, Alfitra; Herlambang, Muhammad (PAKAR Pendidikan, 2024)
In the 17th century, there were two critical moments in the history of world civilization, namely the beginning of the rise and dominance of the West and the beginning of the decline and destruction of Islam in Arabia after its glory for several centuries. For this reason, Arab intellectuals began to examine the causes of this decline and devise solutions to rise again. Then came one of the Arab intellectuals who provided critical solutions and impacted Islamic thought, Muhammad Abid al-Jabiri. He provides ideas from Bayani, Irfani, and Burhani epistemology, which have implications for the revival of Islam, including Islamic education. This research is analyzed theoretically to describe the construction of al-Jabiri's thoughts on Bayani, Irfani, and Burhani epistemology and their correlation with Islamic education. This research aims to overcome the existing knowledge deficit and investigate the impact of epistemology on the criticism of Arabic language education reasoning and its correlation with Islamic education. The research method used is a literature study by taking primary data from Muhammad Abed Al-Jabiri's work entitled "Takwin al-'Aql al-'Arabi". The results show that Bayani, Irfani, and Burhani epistemologies criticize the dominant Arabic reasoning, explore less noticed aspects, and offer more inclusive thinking alternatives in the context of Islamic education. This research also opens a new paradigm on the relationship between these epistemologies and Islamic education. By understanding Arabic reasoning deeply and applying epistemological principles in Islamic education, Islamic education can become more holistic, inclusive, adaptive to the modern world, and develop critical thinking.